Enhancing the Market Value of MSMEs Products through Packaging Improvement in Buluh Duri Tourism Village, Serdang Bedagai, North Sumatra, Indonesia - Dina Rosari; Abdul Kadir Ritonga; Daniel Sihombing (Dinasti International Journal of Education Management And Social Science, 2025)
Buluh Duri Tourism Village in Serdang Bedagai, North Sumatra, is a destination known for its unique MSME (Micro, Small, and Medium Enterprises) products, including traditional food and handicrafts. However, a major challenge for local MSMEs is enhancing the value of their products through attractive and functional packaging. This study analyzes the role of packaging in increasing the value and appeal of MSME products, particularly in the tourism market. Using a qualitative approach, data was collected through observations, interviews with MSME operators, and document reviews. A SWOT analysis was used to identify the strengths, weaknesses, opportunities, and threats faced by MSMEs in improving their packaging. The findings indicate that attractive and informative packaging has a significant impact on consumers' purchasing decisions, especially among tourists. MSME products with modern, aesthetically pleasing packaging that reflects local culture and includes clear product information tend to attract more buyers and increase sales. However, limited knowledge and financial resources pose barriers for many local businesses in improving their packaging. The study suggests that continuous collaboration between local government, Pokdarwis (tourism awareness groups), and MSME operators is necessary to provide training and financial support for packaging development. Utilizing digital technology and social media as promotional tools is also recommended to enhance visibility and appeal. Additionally, eco-friendly packaging aligns with modern consumer trends.